A Suicidal Woman, Roaming Pigs and a Noisy Trampolinist: Refining the ASBO's Definition of Anti-Social Behaviour - Stuart Macdonald (Modern Law Review, 2006)
This article discusses the definition of anti-social behaviour employed by section 1(1)(a) of the Crime and Disorder Act 1998 for the purposes of the Anti-Social Behaviour Order. It argues that, if the ASBO is to remain at the forefront of the Government's campaign against anti-social behaviour, this section should be amended. The article begins by outlining the claimed benefits of, and critics' concerns about, the definition, arguing that the difference of opinion stems from different views of state power. It then argues that the ASBO has been employed for social control, often at the expense of more constructive forms of intervention, and that this has shown New Labour's willingness to vest enforcement agencies with the wide discretion conferred by section 1(1)(a) to have been misplaced. Finally, it proposes a refined version of section 1(1), which focuses the Order on the cases for which it was purportedly designed whilst maintaining any benefits of the broad definitional approach currently taken in section 1(1)(a).